Purificação e caracterização parcial de uma B-D glicosidase de Artemia franciscana com ação sobre celobiose e lactose - Nascimento, Robério Medeiros do (2008)
-D-glucosidase (EC 3.2.1.21) is one of the most interesting glycosidases, especially for hydrolysis cellobiose releasing glucose, is last step degradation of cellulose. This function makes the -D-glucosidase is of great interest as a versatile industrial biocatalyst, being critical to various bio-treatment / biorefinery processes, such as bioethanol production. Hen in the report, a -D-glucosidase was extracts from protein extracted of the invertebrate marine Artemia franciscana was purified and characterized with a combination of precipitation with ammonium sulfate (0 - 30%, 30 to 50%, 50 to 80%), the fraction saturated in the range of 30 to 50% (called F-II) was applied in a molecular exclusion chromatography, in Sephacryl S-200, the fractions corresponding to the first peak of activity of -D-glucosidase were gathered and applied in a chromatography of ion exchange in Mono Q; the third peak this protein obtained chromatography, which coincides with the peak of activity of -D-glucosidase was held and applied in a gel filtration chromatography Superose 12 where the first peak protein, which has activity of -D-glucosidase was rechromatography on Superose 12. This enzyme is probably multimerica, consisting of three subunit molecular mass of 52.7 kDa (determined by SDS-PAGE) with native molecular mass of 157 kDa (determined by gel filtration chromatography on Superose 12 under the system FPLC). The enzyme was purified 44.09 times with a recovery of 1.01%. Using up p-nitrophenyl-β-D-glucopiranoside as substrate obtained a Km apparent of 0.229 mM and a Vmax of 1.109 mM.60min-1.mL-1mM. The optimum pH and optimum temperature of catalysis of the synthetic substrate were 5.0 and 45 °C, respectively. The activity of the -D-glucosidase was strongly, inhibited by silver nitrate and N- etylmaleimide, this inhibition indicates the involvement of radical sulfidrila the hydrolysis of synthetic substrate. The -D-glucosidase of Artemia franciscana presented degradativa action on celobiose, lactose and on the synthetic substrate -nitrophenyl-β-D-glucopiranoside indicating potential use of this enzyme in the industry mainly for the production of bioethanol (production of alcohol from the participating cellulose), and production hydrolysate milk (devoid of milk lactose)